Scattering by many small particles and creating materials with a desired refraction coefficient. - Andriychuk, M. I.; Ramm, Alexander G. (My University, 2010)
Combining an asymptotic method and computational modelling the authors propose a method for creating materials with the desired electrodynamical characteristics, in particular, with a desired refraction coefficient. The problem of wave scattering by many small particles is solved asymptotically under the assumptions ka 1, d a, where a is the size of the particles and d is the distance between the neighbouring particles. On the wavelength one may have many small particles. Impedance boundary conditions are assumed on the boundaries of small particles. The results of numerical simulation show good agreement with the theory. Constructive conclusions are given for creating materials with a desired refraction coefficient on the basis of the obtained numerical results. Engineering realisation of the theory is of practical interest.
Keywords: many-body wave scattering problem; desired refraction coefficient; computational modelling; materials creation; electrodynamics